2022
DOI: 10.1177/0958305x221109949
|View full text |Cite
|
Sign up to set email alerts
|

How do renewable energy consumption, financial development, and technical efficiency change cause ecological sustainability in European Union countries?

Abstract: Achieving ecological sustainability is a critical issue of the current era, and researchers are striving to find viable solutions for sustainable development and ecological wellbeing. This study is an effort to examine the ecological consequences of renewable energy (REC), financial development (FD), and technical efficiency (TE) in 27 countries of the European Union (EU), time ranges from 1980 to 2018. We used second-generation econometric techniques to consider the cross-sectional dependency in the model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Following the determination of CSD and SLH, the CS‐ARDL is the best strategy for long‐term correlation. This technique estimates dynamic common correlation effects for time dynamics, CSD‐SLH and error cross‐country dependence and investigates short‐ and long‐run estimation (Zhen et al, 2022). The CS‐ARDL common elasticity coefficients contribute to a shared policy framework for environmental sustainability.…”
Section: Methodsmentioning
confidence: 99%
“…Following the determination of CSD and SLH, the CS‐ARDL is the best strategy for long‐term correlation. This technique estimates dynamic common correlation effects for time dynamics, CSD‐SLH and error cross‐country dependence and investigates short‐ and long‐run estimation (Zhen et al, 2022). The CS‐ARDL common elasticity coefficients contribute to a shared policy framework for environmental sustainability.…”
Section: Methodsmentioning
confidence: 99%
“…Ali et al (2021) reached similar conclusions for Vietnam, concluding that fossil fuel consumption is a major contributor to CO 2 emissions. By using the data of European union countries for the period 1980 to 2018, Zhen et al (2022) also concluded that conventional energy resources have adverse impact on environmental quality.…”
Section: Fossil Fuels and Environment Qualitymentioning
confidence: 99%
“…Possibly, the panel cointegration approach is essential that is generally appropriate for the shorter cross-sectional's time-series elements. Recent research (Jianguo et al, 2022;Zhen et al, 2022) has attempted to apply (Westerlund, 2007) the panel cointegration method, which is based on the assumption of CSD. The Westerlund test for panel cointegration accounts for CSD and SLH, which are the critical aspect in panel data estimation (Zhen et al, 2022).…”
Section: Westerlund Cointegrationmentioning
confidence: 99%
See 2 more Smart Citations